1991
DOI: 10.1099/0022-1317-72-12-3017
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Major Antigenic Region on gp55 of Human Cytomegalovirus

Abstract: A major antigenic region localized to the C-terminal part of the 55K glycoprotein of human cytomegalovirus (HCMV) was mapped using synthetic peptides. Analysis of the region with six sera from healthy anti-HCMV seropositive blood donors showed that the length of the reactive sequence varied between four and eight amino acids (aa). The shortest sequence recognized was VTSG (aa 793 to 801 of the 130K precursor protein), but most sera required the three or four residues C-terminal to this to react, giving a major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Much work has been directed at defining immunologically relevant epitopes on the protein (for example see Silvestri et al, 1991). These reports have been abstracted as MAb reactivities in Table 2.…”
Section: R R Spaete R C Gehrz and M P Landinimentioning
confidence: 99%
“…Much work has been directed at defining immunologically relevant epitopes on the protein (for example see Silvestri et al, 1991). These reports have been abstracted as MAb reactivities in Table 2.…”
Section: R R Spaete R C Gehrz and M P Landinimentioning
confidence: 99%
“…These studies indicate that certain regions of the molecule are immunodominant in humans [Kniess et al, 1991;Silvestri et al, 1991;Utz et al, 1989;Wagner et al, 1992]. Following immunization with a live HCMV vaccine or a subunit gB vaccine, both recipients have IgG and secretory IgA to HCMV gB with comparable levels of virus neutralizing activity .…”
Section: Introductionmentioning
confidence: 99%
“…Gp58 represents the C-terminal part of the precursor protein and most likely functions as the transmembrane protein, whereas gpll6 corresponds to the N-terminal half (Mach et al, 1986;Meyer et al, 1990;Kari et al, 1990). Studies utilizing immunoblot analyses of prokaryotic fusion proteins and human convalescent sera have revealed that only a limited number of linear antibody binding sites is present on the H. Meyer and others gp58/116 gene product (Meyer et al, 1990;Kniess et al, 1991 ;Silvestri et al, 1991). Three major sites have been identified.…”
Section: Introductionmentioning
confidence: 99%